2021
DOI: 10.3390/polym13234219
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cellular Uptake and Transfection of Oligoarginine-Conjugated Glycol Chitosan/siRNA Nanoparticles

Abstract: Chitosan and its derivatives have been extensively utilized in gene delivery applications because of their low toxicity and positively charged characteristics. However, their low solubility under physiological conditions often limits their application. Glycol chitosan (GC) is a derivative of chitosan that exhibits excellent solubility in physiological buffer solutions. However, it lacks the positive characteristics of a gene carrier. Thus, we hypothesized that the introduction of oligoarginine peptide to GC co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…To evaluate HIF2α siRNA incorporation into PAMs, a gel shift assay was performed to compare HIF2α-CD27 PAMs (500 ng siRNA, 13.3 μg PAM) and free HIF2α siRNA (500 ng siRNA) migration [ 36 ]. As shown in Figure 1 D, following 90 min of electrophoresis at 50 V, >95% of HIF2α-CD27 PAMs (lane i) remained in the well, demonstrating that the HIF2α siRNA was successfully incorporated into the micelle.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate HIF2α siRNA incorporation into PAMs, a gel shift assay was performed to compare HIF2α-CD27 PAMs (500 ng siRNA, 13.3 μg PAM) and free HIF2α siRNA (500 ng siRNA) migration [ 36 ]. As shown in Figure 1 D, following 90 min of electrophoresis at 50 V, >95% of HIF2α-CD27 PAMs (lane i) remained in the well, demonstrating that the HIF2α siRNA was successfully incorporated into the micelle.…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan exhibits excellent biocompatibility, due to its low toxicity and immunogenicity, and is widely used in many drug delivery applications (e.g., anticancer drug and gene delivery). [15,16] GC, a soluble derivative of chitosan, has been used as a hydrophilic backbone in many studies. PBA and its derivatives are utilized for glucose-dependent sensors and insulin-delivery systems, as they can reversibly bind to glucose diols in aqueous media.…”
Section: Polymer Micelles With Glucose-capturing Abilitymentioning
confidence: 99%
“…6 It is produced by partial deacetylation of chitin under an alkaline condition and is structured as residue 1 of β- (1,4)-2-amino-2-deoxy-Dglucopyranose and N-acetyl-D-glucosamine. 7 The characteristics of chitosan are biocompatibility, cytocompatibility, bioabsorbability, and biodegradability, so it has been studied in many biomedical fields, such as drug delivery, 8 gene delivery, 9 and transfection and immune adjuvant. 10 Recently, numerous studies have also demonstrated the antibacterial and antioxidant properties of chitosan and its derivatives.…”
Section: Introductionmentioning
confidence: 99%